Antibiotic Susceptibility of Cronobacter spp. Isolated from Clinical Samples - Holý, Ondřej; Alsonosi, Abdlrhman; Hochel, Igor; Röderová, Magdaléna; Zatloukalová, Simona; Mlynárčik, Patrik; Kolář, Milan; Petrželová, Jana; Alazraq, Aiyda; Chmelař, Dittmar; Forsythe, Stephen (Polish journal of microbiology, 2019)
Cronobacter spp. have been recognized as causative agents of various severe infections in pre-term or full-term infants as well as elderly adults suffering from serious underlying disease or malignancy. A surveillance study was designed to identify antibiotic resistance among clinical Cronobacter spp. strains, which were isolated from patients of two hospitals between May 2007 and August 2013. Altogether, 52 Cronobacter spp. isolates were analyzed. Although MALDI-TOF mass spectrometry recognized all Cronobacter sakazakii and Cronobacter malonaticus strains, it could not identify Cronobacter muytjensii strain. Nevertheless, all strains were identified as Cronobacter spp. using multilocus sequence typing (MLST). Strains were tested against 17 types of antibiotics, using the standard microdilution method according to the 2018 European Committee on Antimicrobial Susceptibility Testing criteria. Three Cronobacter species were identified as C. sakazakii (n = 33), C. malonaticus (n = 18), and C. muytjensii (n = 1); all isolates were susceptible to all tested antibiotics. All strains were PCR-negative for bla TEM, bla SHV, and bla CTX-M β-lactamase genes, as well. Even though the results of this study showed that Cronobacter spp. isolates were pan-susceptible, continued antibiotic resistance surveillance is warranted. Cronobacter spp. have been recognized as causative agents of various severe infections in pre-term or full-term infants as well as elderly adults suffering from serious underlying disease or malignancy. A surveillance study was designed to identify antibiotic resistance among clinical Cronobacter spp. strains, which were isolated from patients of two hospitals between May 2007 and August 2013. Altogether, 52 Cronobacter spp. isolates were analyzed. Although MALDI-TOF mass spectrometry recognized all Cronobacter sakazakii and Cronobacter malonaticus strains, it could not identify Cronobacter muytjensii strain. Nevertheless, all strains were identified as Cronobacter spp. using multilocus sequence typing (MLST). Strains were tested against 17 types of antibiotics, using the standard microdilution method according to the 2018 European Committee on Antimicrobial Susceptibility Testing criteria. Three Cronobacter species were identified as C. sakazakii (n = 33), C. malonaticus (n = 18), and C. muytjensii (n = 1); all isolates were susceptible to all tested antibiotics. All strains were PCR-negative for bla TEM, bla SHV, and bla CTX-M β-lactamase genes, as well. Even though the results of this study showed that Cronobacter spp. isolates were pan-susceptible, continued antibiotic resistance surveillance is warranted.
Keywords: Multilocus Sequence Typing; Drug Resistance, Multiple, Bacterial; polymerázová řetězová reakce; Gram-Negative Bacterial Infections; Genotype; techniky typizace bakterií; mnohočetná bakteriální léková rezistence; Poland; antibakteriální látky; Microbial Sensitivity Tests; Cronobacter sakazakii; lidé; Anti-Bacterial Agents; Cronobacter; Humans; mikrobiální testy citlivosti; gramnegativní bakteriální infekce; multilokusová sekvenční typizace; Bacterial Typing Techniques; genotyp; Polymerase Chain Reaction; Polsko